Association of sugary food consumption, self-perception of dental health status, and dental health awareness with dental caries and gingivitis among rural school children aged 12 years - An analytical cross-sectional study in Nellore District, Andhra Pradesh, India, 2020 - Chandrasekhara Reddy Vuyyuru; Manickam Ponnaiah; Rajeshree Narayan Rangari (Wolters Kluwer Medknow Publications, 2023)
Background and Objectives: Data on the prevalence of dental caries and gingivitis among Indian rural children are scarce. Hence, we estimated the prevalence of dental caries, gingivitis, and associated factors among the rural school children aged 12 years of Nellore district, Andhra Pradesh. Methods: We conducted this analytical cross-sectional study, with 1513 children by following two-stage cluster sampling. We collected data on dental caries and gingivitis using the WHO dentition status and community periodontal index modified, respectively, and associated factors by direct interviews using standardized semi-structured interview guide. We estimated the prevalence of dental caries and gingivitis and 95% confidence interval (CI); we calculated prevalence ratios (PRs) and its 95% CI by comparing factors among those with and without caries and gingivitis; we computed adjusted PRs using the generalized linear regression model. Results: Overall prevalence of dental caries and gingivitis was 61% (95% CI: 58-63) and 68% (95% CI: 65-70), respectively. Sugary food consumption (PR 1.56, 95% CI 1.33-1.82), fair and poor perception of the current dental health status (PR 1.31 95% CI 1.19-145 and PR 1.59 95% CI 1.45-1.73, respectively), and no dental health awareness (PR 0.85 95% CI 0.75-0.95) were associated with caries. Fair and poor perception of current dental health status (PR 1.16 95% CI 1.07-1.26 and PR 1.27 95% CI 1.17-1.38, respectively) was associated with gingivitis. Conclusion: We observed a high prevalence of dental caries and gingivitis among the study participants. Sugary food consumption, dental health awareness, and perception of current dental health status are associated with dental caries and gingivitis.